The Very Best Bed - Raye, Rebekah (Gardiner, ME Tilbury House, 2006)
The busy gray squirrel is ready for bed, but he's wondering where he will sleep tonight. He finds a cozy den, but a big black bear is already sleeping there. On his way up a tree, he sees a family of bats, but sleeping upside down makes his head ache. A beaver slaps his tail on the water before he dives down to his bed in his lodge, but the squirrel doesn't want to get his fluffy tail wet.
K - 2
Keywords: Forest animals - Fiction